Analysis of heart rate variability in patients with chronic alcohol abuse - Gozhenko, A. I.; Petrov, V. A. (Journal of Education, Health and Sport, 2015)
Article represents the results of studies on the use of the method of assessment of heart rate variability in patients with alcohol withdrawal syndrome without delirious syndrome and in patients with the condition as a result of alcohol withdrawal with delirium tremens in the intensive care unit. The studies were conducted on the first day of hospitalization in both groups of patients in the clinic. These data were compared with the norms of the corresponding options of heart rate variability and among themselves. The results indicate a significant autonomic dysfunction in patients with chronic alcohol dependence. The study determined the correlation between heart rate variability and hemodynamics in both groups.